Priority queuing for real time services in diffserv IPv6 network - Chowdhury, Md. Asasul Islam (2005)
In real-time communication, the quality of services depends on the time at which messages are successfully delivered to the recipients. Quality of Service (QoS) requirements is typically formulated in terms of performance metrics such as Bandwidth, End-to-End Delay, Delay Jitter, and Packet Loss. Bandwidth is the average number of bits per second that can travel successfully through the network. Delay jitter, which is the maximum variation in delay experienced by packets in a single connection. In recent years, a number of new classes of distributed applications have emerged, such as remote video, multimedia conferencing, data fusion, visualization, and virtual reality. The development from data-oriented to multimedia services, i.e., from non-real-time to realtime service, requires the QoS guarantees instead of best-effort-delivery. In order to provide service guarantees, some level of quantifiable reliability, IP services must be supplemented with the ability to differentiate traffic and enable different service levels for different users and applications. This work includes developing an IPV6 network with Diffserv. The Diffserv network allows the option to priorities the data packets according to the content. Every packets that enter the Diffserv region, examined and set the priority code at their header field (called TOS) according to the priority of the packet data. This ensures the priority flow of the data to the next hop/router. To differentiate the priority of the data from the default one, the extra traffic is generated to the network. The performance of the system investigated and analyzed according to the Quality of Service CODE in the every packet, which has been assigned according to the priority of data.